Postpartum ovarian vein thrombosis presenting as ureteral obstruction. (10th August 2010) - Kolluru, Anuradha; Lattupalli, Rakesh; Kanwar, Manreet; Behera, Deepak; Kamalakannan, Desikan; Beeai, Muhammed K
Abstract : Ovarian vein thrombosis (OVT) is a relatively uncommon but serious postpartum complication. Although infrequent, OVT may progress to involve the inferior vena cava, the renal vein or may cause sepsis and septic pulmonary embolism, all of which are potentially life-threatening. Clinical misdiagnosis is common, and, unfortunately, most affected women undergo laparotomy for possible appendicitis. We present an interesting case of OVT presenting as ureteral obstruction in a postpartum woman who was in her early 20s. Knowledge of this entity and clinical suspicion for its occurrence, in a puerperal patient with fever and abdominal pain not responding to antibiotics, should guide clinicians to appropriate diagnosis and treatment, avoiding misdiagnosis, unnecessary laparotomy and potential complications.